Mutagenesis of the glucocorticoid receptor in mice - Kellendonk, Christoph; Tronche, François; Reichardt, Holger Michael; Schütz, Günther (The journal of steroid biochemistry and molecular biology, 1999)
The glucocorticoid receptor is an ubiquitously expressed transcription factor involved in the regulation of many different physiological processes. Activated by glucocorticoids the receptor regulates transcription positively or negatively either by direct binding to DNA or by protein–protein interactions. In order to define the role of the receptor during development and in physiology several mutations have been generated in the mouse. Mice with a disrupted glucocorticoid receptor gene die shortly after birth due to respiratory failure indicating an important role of the receptor in lung function. Transcription of genes encoding gluconeogenic enzymes in the liver is decreased, proliferation of erythroid progenitors is impaired and the HPA axis is strongly upregulated. To analyze molecular mechansims of glucocorticoid receptor action in vivo a point mutation has been introduced into the mouse genome which allows to separate DNA-binding-dependent from DNA-binding-independent actions of the receptor. Mice homozygous for the point mutation survive indicating that DNA-binding of the receptor is not required for survival. Induction of glucoconegenic enzymes and proliferation of erythroid progenitors however is impaired. Interestingly, repression of corticotropin releasing factor (CRF) synthesis is maintained, whereas proopiomelanocortin (POMC) expression is upregulated. Since mice with a disrupted glucocorticoid receptor gene die shortly after birth attempts using the Cre/loxP-recombination system are made to bypass early lethality and to study the function of the receptor in defined cell types of adult animals.